THE PURPOSE OF REGIONAL DEVICES IN THE ERA OF REGIONAL AUTONOMY TO ACHIEVING STRONG FOOD RESERVES - Lihawa, Harlan H. (Bajang Institute, 2024)
This study aims to analyze the functions and roles of regional organizations in supporting local governments, specifically in managing food reserves in South Bolaang Mongondow Regency during the era of regional autonomy. The research adopts a normative legal method, focusing on legal literature related to regional autonomy and food security laws. The study also incorporates empirical data, particularly the Food Security Index, to assess the challenges posed by natural disasters and infrastructural limitations in maintaining adequate food reserves. The results highlight that local governments face significant obstacles, including geographical vulnerabilities and resource limitations, which hinder food security. The findings suggest that strategic reforms and enhanced cooperation between regional and local governments are necessary to achieve sustainable food security in disaster-prone areas.